UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MODEL KOOPERATIF STAD PADA SISWA KELAS V SD NEGERI 005 BANGUN PURBA TAHUN PELAJARAN 2015/2016 - Megawati Megawati (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to improve mathematics learning outcomes in performing integer counting operations in SDN 005 Bangun Purba using STAD Co-operative (Student Team Achievement Division) model. The type of this research was Classroom Action Research (PTK) in SDN 005 Bangun Purba with sample that is student of class V SDN 005 Bangun Purba. This study consists of 2 cycles, while each cycle is done in 2 meetings. The results of this study found that by considering the comparison of student learning outcomes in cycle 1 and cycle 2 that there was an increase in mathematics learning outcomes with STAD cooperative model in grade V students SDN 005 Bangun Purba.